The Sensitivity of Arctic Ozone Loss to Polar Stratospheric Cloud Volume and Chlorine and Bromine Loading in a Chemistry and Transport Model - Strahan, S. E.; Douglass, A. R.; Stolarski, R. S.; Polansky, B. C. (2006)
The sensitivity of Arctic ozone loss to polar stratospheric cloud volume (V(sub PSC)) and chlorine and bromine loading is explored using chemistry and transport models (CTMs). A simulation using multi-decadal output from a general circulation model (GCM) in the Goddard Space Flight Center (GSFC) CTM complements one recycling a single year s GCM output in the Global Modeling Initiative (GMI) CTM. Winter polar ozone loss in the GSFC CTM depends on equivalent effective stratospheric chlorine (EESC) and polar vortex characteristics (temperatures, descent, isolation, polar stratospheric cloud amount). Polar ozone loss in the GMI CTM depends only on changes in EESC as the dynamics repeat annually. The GSFC CTM simulation reproduces a linear relationship between ozone loss and Vpsc derived from observations for 1992 - 2003 which holds for EESC within approx.85% of its maximum (approx.1990 - 2020). The GMI simulation shows that ozone loss varies linearly with EESC for constant, high V(sub PSC).